2020
DOI: 10.1001/jamainternmed.2019.6447
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ticagrelor vs Clopidogrel With Major Adverse Coronary Events in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention

Abstract: IMPORTANCE Guidelines currently recommend ticagrelor over clopidogrel for patients with acute coronary syndrome (ACS) based on randomized clinical trial data in which ticagrelor reduced major adverse coronary events (MACE) vs clopidogrel but increased bleeding and dyspnea.OBJECTIVE To compare the risk of MACE with ticagrelor vs clopidogrel in patients with ACS treated with percutaneous coronary intervention (PCI), to compare major bleeding and dyspnea, and to evaluate the association between P2Y 12 inhibitor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 26 publications
10
75
3
2
Order By: Relevance
“…More interestingly, several recent real‐world studies actually found that ticagrelor was not superior to clopidogrel for preventing ST, 38‐40 which was different from PLATO trial as well as our study. This might be explained by the following reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…More interestingly, several recent real‐world studies actually found that ticagrelor was not superior to clopidogrel for preventing ST, 38‐40 which was different from PLATO trial as well as our study. This might be explained by the following reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…This might be explained by the following reasons. A potent mediator for efficacy attenuation of ticagrelor outside RCT might be decreased compliance because of the higher rate of adverse events (dyspnea, bleeding), administration of the drug twice daily and higher costs 38‐40 . Additionally, the overall improvement in the clinical outcomes of patients with ACS 41 might be another possible explanation for the diminished benefit of ticagrelor in the modern era; particularly, this might be driven by progress in the use of drug‐eluting stents 42 and poststenting care.…”
Section: Discussionmentioning
confidence: 99%
“…This is not dissimilar to the previously published real-world data; Schwalm et al reported a 92% compliance in P2Y12 inhibitor prescriptions after PCI in a cluster RCT, while and Turgeon et al demonstrated a 80.5% compliance rate in their cohort of 13,897 ACS patients treated with PCI in Alberta from 2012 to 2016. (28,29) Esposti et al analysed discharge prescriptions of 1,882 ACS patients in Italy. Of the 83% of patients who were discharged on any antiplatelet therapy, 57% were prescribed ASA and clopidogrel and only 0.1% of patients were discharged on ASA and ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…В качестве примера можно отметить неожиданные результаты ретроспективного анализа баз данных страховых компаний, который был выполнен в Германии с использованием метода PS [30]. В ходе выполнения анализа, включавшего данные о 37439 пациентах с ФП, были получены данные о том, что прием варфарина по сравнению с ППОАК сопровож дается меньшей часто- [31]. Полученные результаты свидетельствовали о том, что применение тикагрелора в клинической практике не имеет преимуществ по сравнению с приемом клопидогрела по влиянию на риск развития тяжелых осложнений коронарной болезни сердца в течение года после стентирования коронарной артерии по поводу острого коронарного синдрома.…”
Section: современные подходы к уменьшению ограничений обсервационных unclassified